PENGARUH UKURAN PARTIKEL EKSTRAK KINA (CINCHONA LEDGERIANA) DAN ALAMANDA (ALLAMANDA CATHARTICA) TERHADAP BERBAGAI AKTIVITAS SECARA IN VITRO - Ernest Sukarwan, Adrianus
Extract of cinchona and allamanda contains various therapeutic compounds. Dried extract of cinchona and allamanda, which obtained by maceration with ethyl acetate, were formulated in nanosuspension, with the aim of knowing the influence of its particle size reduction to several activity. Nanosuspension was prepared using evaporative precipitation principle, and evaluation against particle size, stability and activity as antioxidant, tyrosinase enzyme inhibitor and xanthine oxidase enzyme inhibitor were performed. The particle size of 0,5 % cinchona extract nanosuspension was 180,4 nm, and the particle size of 0,25 % allamanda extract nanosuspension was 101,3 nm. Stability test revealed that the nanosuspension was stable within 20 days. Antioxidant activity testing was performed by determining IC50 from DPPH damping. The IC50 value of cinchona extract is 55.2 ± 0.6 ?g / ml, the cinchona nanosuspension is 79.8 ± 1.8 ?g / ml. The IC50 of the allamanda extract is 62.20 ± 4.4 ?g / ml, and allamanda nanosuspension is 96, 7 ± 2.7 ?g / ml. The IC50 value of the allamanda extract is 20.0 ± 1.8 ?g / ml and the IC50 of allamanda nanosuspension is 22.2 ± 1.1 ?g / ml for tryrosinase enzyme inhibitory. The inhibitory value of the tyrosinase enzyme by cinchona extract is 30.1 ± 1.5 %, whereas the nanosuspension inhibition value is 23.4 ± 2.0 %. Then, the determination of the xanthin oxidase enzyme inhibition activity was performed on allamanda extract and allamanda nanosuspension at 100 µg/ml, that is 28,9 ± 2,3% and 67,7 ± 2,3% respectively. Nanosuspension increase xanthine oxidase enzyme inhibitor activity, but it has no effect on antioxidant and tyrosinase enzyme inhibitor activity.